Penguatan Pemasaran dan Pengembangan Kemasan Produk UMKM Sempol Bagong: Sebuah Pendekatan Pendampingan Berbasis Masalah - Cici Anggraini; Go Gunawan Santoso; Malvin Dharma; Sudarmiatin Sudarmiatin; Yuli Soesetio (FKIP, Universitas Palangka Raya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in supporting the Indonesian economy, but still face many limitations in terms of marketing and product packaging. This article presents the results of mentoring Sempol BAGONG MSMEs in Malang City who are engaged in sempol-based food products in the form of frozen food and ready-to-eat cooked products. The assistance is focused on strengthening marketing strategies, optimizing digital marketing, redesigning frozen product packaging, developing mature product packaging, and utilizing halal certificates as added value for branding. The method used is a participatory qualitative approach through observation, in-depth interviews, and direct intervention on prioritized business aspects. The results of the assistance show an increase in MSME marketing capacity, packaging attractiveness, and digital promotion reach. In addition, halal certificates have been proven to provide added value in building consumer trust. This finding is in line with previous research that confirms that packaging innovation and the use of digital media contribute significantly to increasing the competitiveness of food MSMEs. Thus, this assistance provides practical implications for strengthening MSMEs through creative marketing strategies, packaging innovation, and sustainable use of digital technology.